Lesion of the thoracic tract and trachea caused by non-penetrating trauma of the thorax - Fronzuti, Agustín; Martínez, José Luis; Giorgi, Pedro; Quiroz, Darío (Cirugía del Uruguay, 1984)
description o! an unusual case o! section o! the thoracic channel associated with a tracheobroncheal longitudinal lesion caused by non-penetraling trauma o! the thorax. The lesion o! the thoracic channel originated a tension chylothorax encysted by prior pleural adhesions, and simulated a hemomediastinum